2021
DOI: 10.1001/jamaoncol.2020.7310
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immunophenotype With Pathologic Complete Response to Neoadjuvant Chemotherapy for Triple-Negative Breast Cancer

Abstract: Adding carboplatin to standard neoadjuvant chemotherapy (NAC) in triple-negative breast cancer (TNBC) likely benefits a subset of patients; however, determinants of benefit are poorly understood.OBJECTIVE To define the association of molecular subtype, tumor proliferation, and immunophenotype with benefit of carboplatin added to NAC for patients with stages II to III TNBC. DESIGN, SETTING, AND PARTICIPANTSThis was a prespecified secondary analysis of a phase 3, double-blind, randomized clinical trial (BrighTNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…Unfortunately, no clinical trial data are available using volasertib in combination with chemotherapy in TNBC patients. Nonetheless, by analyzing the recently published BrighTNess phase 3 neoadjuvant clinical trial in which carboplatin was added to standard neoadjuvant chemotherapy for TNBC patients (48), we observed a negative correlation between PLK1 and PLK2 expression in those patients whose tumors achieved a pathological complete response as compared to those with residual disease (Supplemental Figure S12). This provides additional support for the potential clinical relevance of PLK2 loss and carboplatin response.…”
Section: Resultsmentioning
confidence: 93%
“…Unfortunately, no clinical trial data are available using volasertib in combination with chemotherapy in TNBC patients. Nonetheless, by analyzing the recently published BrighTNess phase 3 neoadjuvant clinical trial in which carboplatin was added to standard neoadjuvant chemotherapy for TNBC patients (48), we observed a negative correlation between PLK1 and PLK2 expression in those patients whose tumors achieved a pathological complete response as compared to those with residual disease (Supplemental Figure S12). This provides additional support for the potential clinical relevance of PLK2 loss and carboplatin response.…”
Section: Resultsmentioning
confidence: 93%
“…The most predictive transcripts were PD-L1 and CCL5. Subsequent studies confirmed the predictive value of immunophenotyping and TILs, suggesting a role of the immune system in clearing tumor cells during chemotherapy [92]. Another gene signature consisting of HLF, CXCL13, SULT1E1, and GBP1 in pre-treatment samples predicted the extent of lymphocytic infiltration after NACT [93].…”
Section: Tnbc Subtypes and Current Treatment Optionsmentioning
confidence: 80%
“…New technologies such as multiplex immunofluorescent profiling of the immune microenvironment and whole transcriptome RNA sequencing may also aid the future fine-tuning of sTILs as a predictive marker for pCR. Immunomodulatory mRNA signatures and the PAM50 basal-like profile are associated with significantly higher pCR rates in TNBC [ 42 ]. Immune-associated mRNA signatures were associated with pCR after NAC in the GeparNuevo trial, although they were of limited use to predict the response to additional immune-checkpoint blockade by durvalumab [ 43 ].…”
Section: Discussionmentioning
confidence: 99%